PENINGKATAN HASIL BELAJAR PENDIDIKAN PANCASILA MATERI PERUMUSAN DAN PENETAPAN DASAR NEGARA MENGGUNAKAN PROBLEM BASED LEARNING BERBANTUAN MEDIA INTERAKTIF SDN KEBOLAMPANG - Yulia Melinda Putri; Erika Septianing Rustianti; Susilo Tri Widodo; Nur Indah Wahyuni; Risky Nur Aryanti (STKIP Subang, 2023)
This article is motivated by the low learning outcomes of class IV at SDN Kebolampang on Pancasila Education, material on the formulation and determination of state principles. The aim of this research is to improve class IV learning outcomes at SDN Kebolampang through the application of the Problem Based Learning model with the help of interactive learning media, smart boards and quizizz. The method applied is descriptive qualitative. Research activities were carried out in 2 cycles. Class IV students at SDN Kebolampang consisting of 9 male students and 8 female students were used as research subjects. Data analysis applying the Miles and Huberman model includes activities of collecting data, reducing data, presenting data, and drawing conclusions. Obtaining results is intended to prove the progress of Pancasila education learning outcomes from cycle I to cycle II. The results obtained were that through Problem Based Learning assisted by interactive media, it had an impact on increasing the value of Pancasila education. Individual student cognitive learning outcomes have been proven to improve from initial conditions. The initial condition of students who completed was only 1 student (5.9%), then in cycle 1 it increased to 12 students (70.6%), then in cycle II it increased again to 15 students (88.2%).